Öğretmen Adaylarının Mantıksal ve Uzamsal Düşünme Becerileri: Bölüm, Cinsiyet ve Akademik Performansın Etkisi. - TURGUT, Melih; YENİLMEZ, Kürşat; BALBAĞ, M. Zafer (Mehmet Akif Ersoy University Journal of Education Faculty, 2017)
The aim of this research is to investigate prospective middle school mathematics and science teachers' logical thinking and spatial thinking skills and effects of department, gender and academic performance on such skills within multi variable statistics techniques. Research was conducted with 431 prospective teachers enrolled to two different departments, middle school mathematics and science education programs in an educational faculty of a government university located in western Turkey. Logical thinking and spatial skills tests were used to collect data. A three-way between-subjects analysis of variance, 2 (department) × 2 (gender) × 5 (academic performance), was employed to data and according to results, it was observed that while prospective teachers' logical thinking ability was high, their spatial thinking skills were low level. Generally, there was a significant effect of enrolled department on prospective teachers' logical and spatial thinking skills. Next, there were also significant effects of gender and academic performance on spatial thinking skill and a majority of sub-skills of logical thinking were positively correlated to spatial thinking. Interactions among independent variables failed to reach significance for being a factor effecting prospective teachers' logical and spatial thinking skills.